2010
DOI: 10.1021/jm100425v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and Structure−Activity Relationships of Dithiolethiones as Inducers of Cytoprotective Phase 2 Enzymes

Abstract: Dithiolethiones are a family of promising cancer chemopreventive agents, and induction of Phase 2 enzymes is key to their chemopreventive activities. Two dithiolethiones have been evaluated in humans for cancer prevention. While some chemopreventive activities were detected in several human studies, potential side effects are a concern. Herein, we report structure-activity relationships of 25 dithiolethiones. Several compounds show exceedingly potent and bladder specific activity in Phase 2 enzyme induction. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Another study has shown that MIC-1 (also called moringin) significantly increases the nuclear expression of Nrf2 in LPS-stimulated macrophages (Rajan et al, 2016), supporting the direct regulation of Nrf2 by MIC-1. In this study, MSE significantly regulated the gene expression of iNOS and NQO1 in vivo , which are associated with chronic inflammation, oxidative stress, and obesity-induced insulin resistance in mice (Fujimoto et al, 2005; Munday et al, 2010; Shinozaki et al, 2011), supporting the role of MIC-1 as the primary bioactive component of MSE and the mechanism by which MSE improved the glucose tolerance and overall metabolic health of the mice.…”
Section: Discussionsupporting
confidence: 65%
“…Another study has shown that MIC-1 (also called moringin) significantly increases the nuclear expression of Nrf2 in LPS-stimulated macrophages (Rajan et al, 2016), supporting the direct regulation of Nrf2 by MIC-1. In this study, MSE significantly regulated the gene expression of iNOS and NQO1 in vivo , which are associated with chronic inflammation, oxidative stress, and obesity-induced insulin resistance in mice (Fujimoto et al, 2005; Munday et al, 2010; Shinozaki et al, 2011), supporting the role of MIC-1 as the primary bioactive component of MSE and the mechanism by which MSE improved the glucose tolerance and overall metabolic health of the mice.…”
Section: Discussionsupporting
confidence: 65%
“…PAM-PIleOtBu block copolymer (12). 400 mg (25 mmol) of (10), 224 mg (1.25 mmol) of EPHP and 2.05 mg (12.5 mmol) of AIBN were dissolved in 2.5 mL of DMF.…”
Section: Synthesis Of the Pam-gly And Pam-ile Polymersmentioning
confidence: 99%
“…Despite their potential in cancer therapy and prevention, clinical trials of dithiolethiones such as Oltipraz resulted in a questionable efficacy and significant side effects . Toward improved chemopreventive effects, considerable efforts have been made to synthesize different dithiolethione derivatives that are more effective in inducing phase II enzymes . However, potential problems would be unfavorable pharmacokinetics due to the rapid spreading throughout the body and lack of tissue specificity, which are often associated with the use of low‐molecular weight drugs.…”
Section: Introductionmentioning
confidence: 99%
“…GSH is the main cellular antioxidant and works by donating reducing equivalents and conjugating with electrophiles via GST catalysis in phase II detoxification reactions; therefore, its role is fundamental in the elimination of xenobiotics and reactive oxygen species (ROS) [ 6 , 7 ]. It was also reported that ADT can activate Nrf2, which is a major transcriptional stimulator of antioxidant and cytoprotective genes and is critical for cancer prevention [ 8 ].…”
Section: Introductionmentioning
confidence: 99%